Corporate Governance and Firm Performance: Empirical Evidence from India (Journal of Business and Management Research, 2016)
The paper attempts to analyze inter-linkages between corporate governance, ownership structure, capital structure and firm performance in India. The study employs a panel data of all CNX Nifty companies from 2008 to 2012. Using LSDV panel data models and 2SLS model the study reveals that that good corporate governance practices adopted by companies is positively related with financial performance. Board independence, number of board committees, and director remuneration are found to have positive relationship while larger board size, ownership by promoters and financial leverage have negative relationship with performance. There is existence of bi-directional relationship between corporate governance and financial performance. Companies with sound financial performance are more likely to conform to corporate governance norms and standards and implement sound corporate governance system. In addition, the findings reveal that corporate governance practices adopted by the listed firms depend on their ownership structure. Ownership concentration is found to effect corporate governance negatively.Journal of Business and Management Research, Vol. 1 (2), 2016, pp. 48-65.